The role of context in counterfactual thinking - Walsh, Clare (Trinity College (Dublin, Ireland). School of Psychology, 2002)
The aim of this thesis is to examine the mental representations and cognitive processes involved in counterfactual thinking, that is, in imagining how past events might have happened differently. In chapter 1, we review the functions of counterfactual thinking, the types of counterfactuals people generate most readily and the mental representation of counterfactuals. We describe two broad theories of the processes underlying counterfactual thinking, which we term the focus theory and the context theory.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin